Development of multi-directional real-time hybrid simulation for tall buildings subject to multi-natural hazards - Al-Subaihawi, Safwan; Ricles, James; Quiel, Spencer; Marullo, Thomas (Engineering structures, 2024)
Real-time hybrid simulation (RTHS) divides a structural system into analytical and experimental substructures that are coupled through their common degrees of freedom. This paper introduces a framework to enable RTHS to be performed on 3D nonlinear models of tall buildings with rate dependent nonlinear response modification devices, where the structure is subjected to multi-directional wind and earthquake natural hazards. A 40-story tall building prototype with damped outriggers is selected as a case study. The analytical substructure for the RTHS consists of a 3-D nonlinear model of the structure, where each member in the building is discretely modeled in conjunction with the use of a super element. The experimental substructure for the RTHS consists of a full-scale rate-dependent nonlinear viscous damper that is physically tested in the lab, with the remaining dampers in the outrigger system modeled analytically. The analytically modeled dampers use a stable explicit non-iterative element with an online model updating algorithm, by which the covariance matrix of the damper model’s state variables does not become ill-conditioned. The damper model parameters can thereby be updated in real-time using measured data from the experimental substructure. The explicit MKR-α method is optimized and used in conjunction with the super element to efficiently integrate the condensed equations of motion of a large complex model having more than 1000 nonlinear elements, thus enabling multi-axis earthquake and wind hybrid nonlinear simulations to be performed in real-time. An adaptive servo-hydraulic actuator control scheme is used to enable precise real-time actuator displacements in the experimental substructure to be achieved that match the target displacements during a RTHS. The IT real-time architecture for integrating the components of the framework is described. To assess the framework, 3D RTHS of the 40-story structure were performed involving multi-axis translational and torsional response to multi-directional earthquake and wind natural hazards. The RTHS technique was applied to perform half-power tests to experimentally determine the amount of supplemental damping provided by the damped outrigger system for translational and torsional modes of vibration of the building. The results from the study presented herein demonstrate that RTHS can be applied to large nonlinear large structural systems involving multi-axis response to multi-directional excitation. •RTHS with discrete nonlinear models of 3D tall buildings subject to natural hazards.•Incorporated super element and optimized explicit integration algorithm for 3D RTHS.•Model updating using Kalman Filter with positive definite formulated covariance.•Wind and earthquake loadings shown to influence servo-hydraulic actuator control.•RTHS half-power method is used to estimate the supplemental damping in the building.